Financial Distress dan Manajemen Laba: Apakah Perusahaan Bermasalah Cenderung Memanipulasi Laba? - Qurasih Ainun Nurul Ussamah; Eni Witanti; Siti Isnaniati (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The purpose of this study is to examine the impact of financial constraints on workforce management practices in agricultural companies listed on the Indonesia Stock Exchange between 2022 and 2025. Earnings management was measured using the DeAngelo Discretionary Accrual model, while financial distress was measured using the Altman Z-Score. A purposive sample yielded 32 observations, and the data were analyzed quantitatively using simple linear regression in SPSS. The analysis results showed that Financial Distress had no significant effect on Earnings Management, with a significance value of 0.718 (>0.05). The coefficient of determination (R²) of 0.004 indicates that only 0.4% of the variation in earnings management practices can be explained by financial distress, while the remaining 99.6% is influenced by factors outside this model. This finding suggests that the adoption of earnings management strategies in pharmaceutical companies is not primarily driven by financial distress. Therefore, it is recommended that future research include additional variables that could potentially influence earnings management.